Valdosta High School Scrapbook 27, December 1978 – May 1979 - Valdosta High School (My University, 1978)
This item contains newspaper clippings and photographs detailing events involving Valdosta High School. The events mainly discuss the men's and women's basketball teams. Other ports like Football and Baseball are mentioned.
This item contains 1 PDF file with 52 Pages and a title page. In addition to 29 JPG files.
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.); Basketball; Distributive Education Clubs of America; American Football; Baseball